Comparing Clinical Characteristics Between Hospitalized Adults With Laboratory-Confirmed Influenza A and B Virus Infection. (18th April 2014) - Su, Su; Chaves, Sandra S.; Perez, Alejandro; D'Mello, Tiffany; Kirley, Pam D.; Yousey-Hindes, Kimberly; Farley, Monica M.; Harris, Meghan; Sharangpani, Ruta; Lynfield, Ruth; Morin, Craig; Hancock, Emily B.; et al.
Abstract : We challenge the notion that influenza B is milder than influenza A by finding similar clinical characteristics between hospitalized adult influenza-cases. Among patients treated with oseltamivir, length of stay and mortality did not differ by type of virus infection.